P Peran Psikologi Olahraga Dalam Meningkatkan Mental Atlet Sepak Bola Fc Prima Selong: bahasa indonesia - Abdullah, Catur Prima Eka Putra; Azhari, Haeruddin (Universitas Hamzanwadi, 2024)
The purpose of this study was to examine the role of sports psychology in improving the mentality of FC Prima Selong soccer athletes. The method used in this research is to use a quantitative descriptive approach. The population of this study was 31 and the sample of this study amounted to 31. The instrument used in this study with a Likert scale approach. The data analysis technique uses the calculation of the percentage of the answer score of the specified variable. The results state that the emotional aspect with a presentation of 59% which is included in the criteria is still quite emotional. However, there are aspects of high motivation with a presentation of 89% which is included in the excellent criteria in athletes, aspects of intelligence 83% with very good criteria, high self-confidence in athletes with a percentage of 88%, and calmness in the criteria is very good with a percentage of 81%. However, there are still aspects of anxiety that fall into the criteria quite anxious with a percentage of 44% in this FC Prima Selong soccer athlete. It is concluded that the role of sports psychology in improving the mentality of athletes is very large. Because in sports psychology will play an important role in improving emotional management, self-confidence, athlete calmness when competing, anxiety, motivation that can improve achievement and the winning mentality of an athlete.